Socio-economic burden of respiratory syncytial viral infection of the lower respiratory tract in children aged from birth to 5 years in the Russian Federation: modeling results - V. I. Ignatyeva; D. Yu. Ovsyannikov; A. E. Tsygankov; E. E. Yagnenkova; V. R. Amirova; M. M. Maryanyan; A. S. Mokrova (IRBIS LLC, 2024)
Background. Respiratory syncytial virus (RSV) is a common virus causing lower respiratory tract infections (LRTI), including acute bronchiolitis and pneumonia, in children in the first 5 years of life.Objective: to estimate the annual socio-economic burden for the Russian Federation (RF) due to RSV-LRTI in children aged under 5 years.Material and methods. Based on published results of meta-analysis of epidemiological data for RSV-induced infections, the annual number of RSV-LRTI cases, the number of hospitalizations, and associated lethal outcomes were calculated in the model for groups of children aged 0 - <12 months, 12 - <24 months, and 24 - 60 months. The costs of medical care were determined according to the current tariffs of the Compulsory Health Insurance system and published Russian data on the distribution of the number of RSV-LRTI cases by severity. The damage to gross domestic product (GDP) associated with fatalities was estimated taking into account life expectancy and employment.Results. According to the estimates, 397.2 thousand children aged under 5 years in the RF fall ill with RSV-LRTI during a year, including 44.6 thousand cases requiring hospitalization, and in 268 cases, the infection becomes lethal. Medical costs for treatment exceed 2.2 billion rubles, and the damage to GDP as a result of lethal outcomes reaches almost 10 billion rubles. The main damage is related to RSV-LRTI cases in children aged under 1 year, the share of which is over 50% among those hospitalized and over 70% among those who died.Conclusion. RSV significantly affects morbidity and mortality among children aged under 5 years. According to modeling data, it causes up to 3.5% of deaths in this age group, and the associated economic losses exceed 12.2 billion rubles, which justifies the need for RSV-LRTI immunoprophylaxis.